THE EXISTENCE OF ARBITRATION INSTITUTIONS FOR PERFORMANCE SPORTS ATHLETE DISPUTES (BAORI, BAKI, NDRC) IN THE PERSPECTIVE OF JUSTICE - Sanusi Sanusi; Efridani Lubis; Abdul Haris Semendawai (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Alternative dispute resolution bodies in the world of sports in Indonesia consist of several entities, namely the Indonesian Sports Arbitration Agency (BAKI), the Indonesian Sports Arbitration Body (BAORI), and the National Dispute Resolution Chamber (NDRC). The process of establishing NDRC Indonesia began with a seminar organized by the Football Association of Indonesia (PSSI) in collaboration with FIFA. Meanwhile, BAORI was established by the National Sports Committee of Indonesia (KONI), and BAKI was initiated by the Indonesian Olympic Committee (KOI). Dispute resolution in the world of sports through arbitration is regulated by Law Number 3 of 2005 concerning the National Sports System. Arbitration institutions such as BAORI, BAKI, and NDRC play a crucial role in resolving various conflicts involving athletes and relevant parties in performance sports in Indonesia. They serve as avenues for seeking justice without going through litigation processes. However, there are challenges in the decisions made by these institutions, where the decisions can favor one party in the dispute or vice versa. In case of dissatisfaction with the decision outcomes, BAKI has a system of appellate bodies that can be utilized, while BAORI and NDRC may lack similar mechanisms. NDRC, as an arbitration institution that focuses more on the sport of football, can be more effective in handling disputes that arise in this performance sport. Moreover, NDRC is affiliated with the Court of Arbitration for Sport (CAS) and has connections with FIFA, making the athlete dispute resolution process more structured compared to other sports that may not have a similar focus like BAORI and BAKI. In terminology, both BAKI and BAORI have equal positions and existences under Law Number 3 of 2005 concerning the National Sports System. Article 88 Paragraph 1 of Law 3/2005 indicates that the resolution of sports disputes should be achieved through consultation and consensus by the parent sports organizations. If consultation and consensus fail, Paragraph 2 states that dispute resolution can be pursued through arbitration or alternative dispute resolution in accordance with the regulations. If all these efforts do not result in a satisfactory resolution, Paragraph 3 states that dispute resolution can be carried out through the appropriate jurisdictional court.